2010
DOI: 10.3390/rs2122748
|View full text |Cite
|
Sign up to set email alerts
|

Application of Object Based Classification and High Resolution Satellite Imagery for Savanna Ecosystem Analysis

Abstract: Savanna ecosystems are an important component of dryland regions and yet are exceedingly difficult to study using satellite imagery. Savannas are composed are varying amounts of trees, shrubs and grasses and typically traditional classification schemes or vegetation indices cannot differentiate across class type. This research utilizes object based classification (OBC) for a region in Namibia, using IKONOS imagery, to help differentiate tree canopies and therefore woodland savanna, from shrub or grasslands. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 70 publications
3
32
0
2
Order By: Relevance
“…However the latter approach had a significantly higher accuracy for almost every classifier with the highest overall accuracy score of 93%. This is consistent with several other studies indicating superiority of using OBIA in a range of environments [5,31,64]. In particular, Whiteside et al (2011) [5] concluded that OBIA outperforms pixel-based classification for medium and high resolution satellite imagery in Australian savannas.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However the latter approach had a significantly higher accuracy for almost every classifier with the highest overall accuracy score of 93%. This is consistent with several other studies indicating superiority of using OBIA in a range of environments [5,31,64]. In particular, Whiteside et al (2011) [5] concluded that OBIA outperforms pixel-based classification for medium and high resolution satellite imagery in Australian savannas.…”
Section: Discussionsupporting
confidence: 81%
“…In particular, Whiteside et al (2011) [5] concluded that OBIA outperforms pixel-based classification for medium and high resolution satellite imagery in Australian savannas. Moreover, study of Gibbes et al (2010) [64] indicates that OBIA has a great potential in discriminating African woodland savanna from shrubby dominated and grassland patches using IKONOS high resolution imagery. Our study goes further, demonstrating that object-based classification of imagery characterized by a small pixel size and 8 spectral bands provides tools for fine level differentiation of spectrally similar vegetation components in the African savanna ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of Geographic Object-Based Image Analysis (GEOBIA) over more traditional pixel-based analyses have been discussed in a number of studies [1][2][3][4]. Whilst a large body of the literature has utilized commercial packages, such as eCognition [5], there is growing interest in open source alternatives [6].…”
Section: Introductionmentioning
confidence: 99%
“…The 12 m crown size was chosen to differentiate between large trees and small trees and bushes, as trees with a crown diameter larger than 12 m are thought to represent keystone species in African savannahs [67]. The different types of man-made constructions above represent various stages in the urban sprawl of Ouagadougou.…”
Section: Comparison Of Data Setsmentioning
confidence: 99%